2019
DOI: 10.1016/j.cgh.2018.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Biologic Therapy in Older Patients With Immune-Mediated Diseases: A Systematic Review and Meta-analysis

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e108. Learning Objective-Upon completion of this activity, successful learners will be able to define the diagnosis, natural history, and treatment of IBD in older individuals. BACKGROUND & AIMS: Management of immune-mediated inflammatory diseases often requires lifelong immunosuppression. Increasing numbers of older patients have inflammatory diseases and are particularly vulnerable to risks of immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 40 publications
5
60
1
Order By: Relevance
“…This result is in contrast with a recent meta‐analysis by Borren et al that has reported a more than 10‐fold higher risk. However, we have included five studies for this outcome, while Borren et al included only three studies (two of them were case‐control studies showing inflated effect estimates), thus we are confident that we have synthesised the current evidence.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…This result is in contrast with a recent meta‐analysis by Borren et al that has reported a more than 10‐fold higher risk. However, we have included five studies for this outcome, while Borren et al included only three studies (two of them were case‐control studies showing inflated effect estimates), thus we are confident that we have synthesised the current evidence.…”
Section: Discussioncontrasting
confidence: 97%
“…The results of the current study are relatively reassuring to clinicians willing to administer biologic drugs to their patients as compared to previous studies on the topic that had found a very elevated risk of infections in elderly IBD patients exposed to biologics . However, clinicians should take into account that sparse evidence showed that the risk of serious and opportunistic infections in older patients may increase further with combination therapy (ie biologics and thiopurines, or biologics thiopurines and corticosteroids) .…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations